Recent advances in the detection of contaminants by portable glucose meter in food samples - Su, Dan; Xu, Longhua; Gao, Shan; Hao, Jianxiong; Zhao, Tao; Hu, Gaoshuang; Wu, Tianqi (FOOD SCIENCE AND TECHNOLOGY RESEARCH, 2023)
Portable glucose meter (PGM) has played vital roles in the field of medicine, with advantages of accurate and quantitative results, portability, easy operation, and low cost. Recently, more and more researchers have extended the application of PGM in detecting foods contaminations. In this paper, a review of the application of PGM based on target recognition elements, such as antibody–antigen reaction, molecularly imprinted polymer, nucleic acid hybridization, enzyme recognition, and click chemistry, and amplification strategies in food safety and contaminant analysis are described in detail. The future development of the application of glucose meters in food safety supervision is also discussed.